1980
DOI: 10.1136/bmj.280.6215.675
|View full text |Cite
|
Sign up to set email alerts
|

Population screening for congenital hypothyroidism.

Abstract: Summary and conclusions A pilot screening programme for congenital hypothyroidism covering most of North London, Essex, Bedfordshire, and Hertfordshire entailed carrying out an assay of thyroid-stimulating hormone on single Guthrie dried blood spots. During one year 87 444 babies were screened and 26 cases of primary congenital hypothyroidism detected, giving an incidence of 1:3363.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 11 publications
(1 reference statement)
1
11
0
1
Order By: Relevance
“…Our recall rate due to raised thyroid stimulating hormone concentrations was similar to those found in other studies.7 221 Of the 31 babies recalled, 12 began thyroxine replacement treatment. The decision to treat was based on the thyroxine concentration together with clinical assessment.…”
Section: Discussionsupporting
confidence: 86%
“…Our recall rate due to raised thyroid stimulating hormone concentrations was similar to those found in other studies.7 221 Of the 31 babies recalled, 12 began thyroxine replacement treatment. The decision to treat was based on the thyroxine concentration together with clinical assessment.…”
Section: Discussionsupporting
confidence: 86%
“…Genetic analysis of several hundred families has shown that the disease closely follows the pattern of autosomal recessive inheritance. 2 The clinical features of familial Mediterranean fever are not present in the newborn, but may appear as early as the first year of life. Over half of sufferers have had an attack by the age of 10 years, and 80-90% by the age of 20.…”
Section: Familial Mediterranean Fevermentioning
confidence: 99%
“…The status of such 'additional' babies and the optimum balance between screening sensitivity and specificity are still matters of debate. Hulse et al (1980), reporting on a pilot study of primary TSH screening in north London, attributed the discrepancy between their screening incidence of 1 in 3,363 births and the expected incidence of 1:6,000 to a greater number of mild cases. "Some of the babies with ectopic thyroid glands would probably have had compensated hypothyroidism for several months or years and would have been classified as cases of juvenile hypothyroidism.…”
mentioning
confidence: 95%